2010
DOI: 10.1116/1.3392039
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescent properties of nanocrystalline Lu3Ga5O12:Tb3+ phosphor for field emission display application

Abstract: The cathodoluminescent properties of nanocrystalline Lu3Ga5O12:Tb3+ phosphor films were investigated. Phosphor films were prepared on indium tin oxide coated glass by a screen printing method. The Lu3Ga5O12:Tb3+ phosphor is mixed with In2O3 nanoparticles to improve the luminescence and degradation properties of phosphor films under electron excitation. Cathodoluminescent spectra and luminance degradation behavior of the Lu3Ga5O12:Tb3+ phosphor films under electron bombardment were studied. Enhancement of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…5(b)) due to the improved penetration depth by the recombination of increased excitons. 35 Because of the deeper penetration depth, more activator ions were excited at almost all parts of the particles including boundaries, surfaces and inside of particles. The electron penetration depth for the CGZO:Tb 3+ nanophosphors was calculated by the following formula: 20,36…”
Section: Resultsmentioning
confidence: 99%
“…5(b)) due to the improved penetration depth by the recombination of increased excitons. 35 Because of the deeper penetration depth, more activator ions were excited at almost all parts of the particles including boundaries, surfaces and inside of particles. The electron penetration depth for the CGZO:Tb 3+ nanophosphors was calculated by the following formula: 20,36…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al also demonstrated that these as-prepared nanocrystalline phosphors (Lu 3 Ga 5 O 12 :Tb 3+ ) by the PSG process can form a more compact phosphor screen, which exhibits an improved luminescent efficiency and stability under the bombardment of an electron beam. 67 Wakefield et al also confirmed that the nanocrystalline oxide based phosphors (Y 2 O 3 :Eu and Zn 2 SiO 4 :Mn) had better luminescence efficiencies than that of commercial FED phosphors, which shows promising properties for use in low voltage field emission displays. 101 Homogenous precipitation process.…”
Section: Improvement Of Phosphor Powdersmentioning
confidence: 94%
“…27 In order to overcome this drawback, in recent years many semiconductor-based materials such as ZnO, Ga 2 O 3 , (Gd,Lu , have been studied as low-voltage cathodoluminescent materials through the efficient doping of RE 3+ , Mn 2+ and Bi 3+ ions. 17,43,[63][64][65][66][67][68][69][70][71][72][73][74][75] Besides, current low voltage cathodoluminescent materials also suffer from rough surfaces, irregular shape and size distributions,…”
Section: Introductionmentioning
confidence: 99%
“…However, the emission intensity of the Tb 3 þ ion is not strong enough to be utilized in commercial phosphor for the f-f transition is spin-forbidden. In recent years, the photoluminescence properties of the Tb 3 þ ions in many hosts have been studied, such as Lu 3 Ga 5 O 12 :Tb 3 þ [7], Y 3 Al 5 O 12 : Tb 3 þ [8]. To enhance the Tb 3 þ ion emission efficiency, the energy transfer from an excited center (energy donor) to an unexcited center (energy acceptor) is often used for the sensitization of luminescence in phosphors.…”
Section: Introductionmentioning
confidence: 99%